To the Problem of the Establishment of Education Science in Ukraine - Кузьменко, Ольга Миколаївна (Educological discourse, 2014)
The article is devoted to the analysis of the factors of the establishment of a new integrated approach to education – educational sciences – in the context of the modern civilizational development’s tendencies of the society.